Distribution of Salmonella in Humans, Production Animal Operations and a Watershed in a FoodNet Canada Sentinel Site. (27th June 2016) - Flockhart, L.; Pintar, K.; Cook, A.; McEwen, S.; Friendship, R.; Kelton, D.; Pollari, F.
Summary: Salmonella is an important human pathogen, and production animals as well as water are known potential sources. This study helped provide insight into the epidemiology of Salmonella by comparing Salmonella strains found in humans to those detected in production animals and water in the same geographic area and time frame. Salmonella was found in 55% of broiler, 30% of swine, 13% of dairy, and 10% of beef manure samples and 23% of water samples. At the farm level, Salmonella was found on 93% of broiler, 81% of swine, 32% of beef and 30% of dairy farms. Salmonella strains of importance to public health were found in all sources tested; however, they appeared to be more common in the broilers. A number of the farms in this study were mixed farms, in that they had more than one production animal species on the farm. At both the sample and farm levels, beef‐only farms had a significantly lower Salmonella prevalence (5% and 7%, respectively) than beef farms with additional production animal species (e.g. poultry) (12% and 42%, respectively) ( P  ≤ 0.05). Additionally, a number of mixed farms had more than one commodity sampled for this study and similar Salmonella strains by phage type and PFGE were found in the poultry and the other sampled commodity on the farm. This information can help inform the evidence base needed to help target interventions and modify best practices in production agriculture.